2021
DOI: 10.1177/17562872211053189
|View full text |Cite
|
Sign up to set email alerts
|

Is there a preferred first-line therapy for metastatic renal cell carcinoma? A network meta-analysis

Abstract: Background: In recent years, new therapeutic combinations based on immunotherapy provided significant benefits as a first-line treatment for patients with advanced renal cell carcinoma (mRCC). Objective: This work aims to address the lack of head-to-head comparisons and the uncertainty of the benefit from immunotherapy-based combinations in all the International Metastatic RCC Database Consortium (IMDC) subgroups. Design, setting, and participants: A systematic review and a network meta-analysis were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The comparators were SUN or standard of care. Three of the ITCs 35,37,38 included outcomes related to efficacy (such as OS and PFS) and safety (TRAEs and treatment discontinuation), and 1 ITC 36 included only studies that reported safety outcomes (TRAEs, treatment discontinuation, and treatment-related mortality).…”
Section: Study Selection Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The comparators were SUN or standard of care. Three of the ITCs 35,37,38 included outcomes related to efficacy (such as OS and PFS) and safety (TRAEs and treatment discontinuation), and 1 ITC 36 included only studies that reported safety outcomes (TRAEs, treatment discontinuation, and treatment-related mortality).…”
Section: Study Selection Methodsmentioning
confidence: 99%
“…36 Two of the published ITCs reported details of the data extraction process either performed or verified in duplicate by 2 independent reviewers. 35,37 Details of the data extraction process were not provided for the other 2 published ITCs. 36,38 In 3 of the 4 published ITCs, the Cochrane risk-of-bias tool was used to assess study quality and, in 1 ITC, study quality was assessed using the Jadad score.…”
Section: Study Selection Methodsmentioning
confidence: 99%
See 3 more Smart Citations